Extrication techniques of entrapped car crash victims: a scoping review - Hamilton Santos Júnior; Bianca Cristina Ciccone Giacon-Arruda; Sarah Larrosa; André Rodrigues de Andrade; Elen Ferraz Teston; Marcos Antonio Ferreira Júnior (SciELO, 2021)
ABSTRACT Objective: to summarize the extrication techniques of entrapped car crash victims with potential spinal injury. Method: a literature review study, of scoping review type, using the MEDLINE/PubMed, CINAHL, Scopus, Science Direct, Web of Science, Cochrane Library and gray literature data sources, without time frame, with studies that addressed extricating techniques extrication of entrapped car crash victims. Results: a total of 33 studies were included that enabled identifying and summarizing the different types of extrication and respective devices for extrication of entrapped car crash victims, indicated according to injury assessment and the victim's clinical condition. All pointed to the need for techniques to maintain neutral alignment and prevent spine twists. Conclusion: this study indicated that injury assessment with an emphasis on the victim's clinical condition provides a coherent decision-making regarding the technique and device to be used. However, carrying out other comparative studies between existing techniques may help in the decision-making process more assertively.